Comorbidity of Affective Disorders and Type 2 Diabetes Mellitus (Eurasian Research Bulletin, 2023)
Mental disorders are among the most common comorbidities with type 2 diabetes, according to various authors, they develop in 70% of patients, which significantly aggravate the course, contribute to an increase in mortality and disability, reduce social and labor rehabilitation and the quality of life of patients. A fairly large spread of data on the prevalence of mental disorders in type 2 diabetes is explained by the inclusion of various categories of syndromes in this group